2020
DOI: 10.1186/s12866-020-01932-2
|View full text |Cite
|
Sign up to set email alerts
|

Differences between predicted outer membrane proteins of genotype 1 and 2 Mannheimia haemolytica

Abstract: Background: Mannheimia haemolytica strains isolated from North American cattle have been classified into two genotypes (1 and 2). Although members of both genotypes have been isolated from the upper and lower respiratory tracts of cattle with or without bovine respiratory disease (BRD), genotype 2 strains are much more frequently isolated from diseased lungs than genotype 1 strains. The mechanisms behind the increased association of genotype 2 M. haemolytica with BRD are not fully understood. To address that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…haemolytica strains (genotype 1 = 10 and genotype 2 = 12; samples were collected from BRDC animals from the states of Kansas, Kentucky, Missouri, and Tennessee in 2013) and four related Pasteurellaceae species Bibersteinia trehalosi (n = 1), Mannheimia glucosida (n = 1), Pasteurella multocida (n = 1), and Histophilus somni (n = 1) were used in this study. Most of the M. haemolytica strains used in this study were molecularly serotyped by PCR in a previous study [ 9 ] and the remaining non-serotyped strains used here were serotyped by rapid plate agglutination test with serotype-specific rabbit antisera generated against ST1 and ST6 as described previously [ 8 ]. Bacterial isolates were grown in trypticase soy agar supplemented with 5% sheep blood (Becton, and Dickinson Co., Sparks, MD) at 37 °C in a humidified atmosphere of 7.5% CO 2 for 16 to 48 h. Genomic DNA of each strain was purified using DNeasy Blood & Tissue Kit as per manufacturer’s instructions (Qiagen Inc, Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…haemolytica strains (genotype 1 = 10 and genotype 2 = 12; samples were collected from BRDC animals from the states of Kansas, Kentucky, Missouri, and Tennessee in 2013) and four related Pasteurellaceae species Bibersteinia trehalosi (n = 1), Mannheimia glucosida (n = 1), Pasteurella multocida (n = 1), and Histophilus somni (n = 1) were used in this study. Most of the M. haemolytica strains used in this study were molecularly serotyped by PCR in a previous study [ 9 ] and the remaining non-serotyped strains used here were serotyped by rapid plate agglutination test with serotype-specific rabbit antisera generated against ST1 and ST6 as described previously [ 8 ]. Bacterial isolates were grown in trypticase soy agar supplemented with 5% sheep blood (Becton, and Dickinson Co., Sparks, MD) at 37 °C in a humidified atmosphere of 7.5% CO 2 for 16 to 48 h. Genomic DNA of each strain was purified using DNeasy Blood & Tissue Kit as per manufacturer’s instructions (Qiagen Inc, Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Angen et al, (1999) suggested that serotyping does not always represent a reliable method to identify M. haemolytica or Mannheimia glucosida isolates [ 6 ]. Recently, M. haemolytica isolated from North American cattle were classified into two genotypes, 1 and 2, based on multiple SNP allele differences and the presence or absence of several genes, such as outer membrane proteins, a peptidase S6, a ligand-gated channel, an autotransporter outer membrane beta-barrel domain-containing protein, a porin, and three different trimeric autotransporter adhesins that were specific to genotype 2 as their homologs were either pseudogenes or completely absent in genotype 1 [ 9 , 10 ]. M. haemolytica genotype 1 is primarily represented by ST2 strains while genotype 2 is primarily represented by ST1 and ST6 strains [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mannheimia haemolytica genotypes 1 and 2 that are identified by this MALDI quick classifier model were previously described by Clawson et al ( 11 ), with genotype 2 isolates primarily originating from the lungs of cattle with clinical or pathological signs of respiratory disease, and typically harboring integrative conjugative elements (ICE) conferring multi-drug antimicrobial resistance, and genotype 1 isolates originating from the upper respiratory tract of cattle with no signs of disease, and typically not including ICE. For strains where there is genomic information available, genotype 1 strains are likely serotype 2 based on molecular analysis and genotype 2 strains are either serotype 1 or serotype 6 based on the same analysis, suggesting a strong relationship between serotype and genotype ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…Strain DNAs were extracted and purified on Qiagen 100/G gravity-flow anion-exchange columns (Qiagen, Valencia, CA, USA) as previously described [51]. The DNAs were quantified using either a Promega Quantus Fluorometer and QuantiFluor Dyes per the manufacturer's instructions (Promega, Madison, WI, USA), or with a DeNovix DS-11FX+ spectrophotometer (Wilmington, DE, USA).…”
Section: Culture Conditions Dna Purification Library Construction And...mentioning
confidence: 99%
“…To confirm phylogenetic relationships, whole genome trees of the 37 M bovis strains were additionally constructed with Parsnp (Harvest version 1.1.2) [59]. As previously described elsewhere [51], Parsnp identifies locally colinear blocks of multi-maximal unique matches which are used to anchor multiple alignments [59]. MUS-CLE was used for generating the alignments [55,56].…”
Section: Phylogenetic Tree Buildsmentioning
confidence: 99%